Characterization of patients with clonal mast cells in the bone marrow with clinical significance not otherwise specifiedResearch in context - Thomas Ballul; Vito Sabato; Peter Valent; Olivier Hermine; Olivier Lortholary; Julien Rossignol; Thomas Ballul; Vito Sabato; Cristina Bulai Livideanu; Antoine Neuraz; Julie Agopian; Fabienne Brenet; et al. (EClinicalMedicine)
Summary: Background: Systemic mastocytosis (SM) diagnosis requires the presence of 3 minor criteria or 1 major and 1 minor criterion according to the WHO 2016 classification. The aim of this study was to characterize patients with 1 or 2 minor SM criteria including KIT 816 mutation and/or aberrant expression of CD2 and/or CD25 on bone marrow (BM) mast cells (MCs), but without MC activation syndrome (MCAS) criteria. Methods: We included eligible patients from two countries diagnosed between 2011 and 2021. These patients are reported herein as monoclonal MC with clinical significance (MMCS). MMCS patients were compared with 432 patients with indolent SM (ISM) and 51 with BM mastocytosis (BMM) from the CEREMAST database. Findings: Overall, 51 patients with MMCS were included. MMCS patients with (n = 29) or without (n = 22) KIT 816 mutation did not differ significantly with regard to the prevalence of anaphylaxis and basal tryptase level. Anaphylaxis, often in the context of hymenoptera venom allergy, was more frequent in MMCS than in ISM (78% vs 35%, respectively; p < 0.001). Osteoporosis was similarly prevalent in MMCS and BMM (45% vs 32%, p = ns). The median baseline serum tryptase level was lower in MMCS compared with ISM or BMM (13 vs 26 vs 23 ng/mL, respectively; p < 0.001). Hereditary alpha-tryptasemia was similarly represented in MMCS and BMM (14.3% vs 19.7% respectively, p = ns). Interpretation: Clonal BMMCs may be associated with clinically relevant symptoms even if criteria for SM or MCAS are not fulfilled. These MMCS patients may require specific management and follow-up to capture potential transition to SM and/or MCAS. Funding: None.